On the Use of Magnetite for Gold Recovery from Chloride Solution - Alorro, Richard; Hiroyoshi, Naoki; Kijitani, Hajime; Ito, Mayumi; Tsunekawa, Masami (Maney Publishing, 2010)
The sorption of gold chloride (AuCl4 ) from chloride solution on synthetic and natural magnetite powders was investigated by batch sorption experiments. The effects of different parameters on the recovery were studied. The results showed that Gold (Au) uptake by magnetite was influenced by pH, contact time, chloride concentration, and initial Au concentration. Gold uptake by synthetic and natural magnetite was maximum at pH 6–7 with sorption amounts of 4.4 lmol/g and 5.0 lmol/g, respectively, after 24 hr at an initial Au concentration of 0.05 mol/m3. The Scanning Electron Microscopy–Energy Dispersive X-ray and Back Scattering Electron analyses of the magnetite particles after treatment confirmed the presence of Au precipitates on the magnetite (Fe3O4) surface.